2018
DOI: 10.1002/ptr.6044
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of 20(S)‐protopanaxatriol (PPT) on scopolamine‐induced cognitive deficits in mice

Abstract: 20(S)-protopanaxatriol (PPT), one of the ginsenosides from Panax ginseng, has been reported to have neuroprotective effects and to improve memory. The present study was designed to investigate the protective effect of PPT on scopolamine-induced cognitive deficits in mice. Male Institute of Cancer Research mice were pretreated with 2 different doses of PPT (20 and 40 μmol/kg) for 27 days by intraperitoneal injection, and scopolamine (0.75 mg/kg) was injected intraperitoneally for 9 days to induce memory impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 27 publications
6
29
0
Order By: Relevance
“…The Western blotting method was performed with slight modification according to our published procedure [ 25 ]. The hippocampus was homogenized on ice in CellLytic™ MT mammalian tissue lysis reagent (Sigma-Aldrich, St. Louis, MO, USA, C3228) containing protease inhibitor cocktail and phosphatase inhibitor cocktail (Sigma-Aldrich, St. Louis, MO, USA, P3840).…”
Section: Methodsmentioning
confidence: 99%
“…The Western blotting method was performed with slight modification according to our published procedure [ 25 ]. The hippocampus was homogenized on ice in CellLytic™ MT mammalian tissue lysis reagent (Sigma-Aldrich, St. Louis, MO, USA, C3228) containing protease inhibitor cocktail and phosphatase inhibitor cocktail (Sigma-Aldrich, St. Louis, MO, USA, P3840).…”
Section: Methodsmentioning
confidence: 99%
“…Compound 4 is an effective compound, and earlier researches have confirmed that it had significant effects, including cardioprotective [21] and antiobesity bioactivities [22]. In recent years, neuroprotective effects of compound 4 were also reported [23,24]. However, this study was the first to evaluate its effects on NDs in an in vitro experimental model.…”
Section: Discussionmentioning
confidence: 83%
“…and Rh2 reduced sleep deprivation-induced memory impairment (Lu et al, 2017;Lu et al, 2018a). Rh1 improved cognition in scopolamine-treated mice using object location, novel object recognition, Morris water maze, and passive avoidance tests.…”
Section: Ginsenoside Rb1mentioning
confidence: 94%
“…These properties are implicated in cognition, but both have shown direct effects on memory and learning. Rh1 and Rh2 reduced sleep deprivation‐induced memory impairment (Lu et al, ; Lu et al, ). Rh1 improved cognition in scopolamine‐treated mice using object location, novel object recognition, Morris water maze, and passive avoidance tests.…”
Section: Ginsenosides Rh1 and Rh2mentioning
confidence: 99%